2008
DOI: 10.4049/jimmunol.181.2.859
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Molecular Basis of Quantitative Trait Loci of Arthritis in Rat: Genes and Polymorphisms

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease, the pathogenesis of which is affected by multiple genetic and environmental factors. To understand the genetic and molecular basis of RA, a large number of quantitative trait loci (QTL) that regulate experimental autoimmune arthritis have been identified using various rat models for RA. However, identifying the particular responsible genes within these QTL remains a major challenge. Using currently available genome data and gene annotation information, we sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…Studies in experimental models have identified many quantitative trait loci (QTLs) that show a significant association with arthritis susceptibility and severity [ 3 - 6 ]. At least 52 QTLs have been identified in different rat models of arthritis, and these QTLs cover approximately 54% of the total rat genome [ 6 ].…”
Section: Genetic Linkage Studies For Adjuvant Arthritis-linked Quantimentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in experimental models have identified many quantitative trait loci (QTLs) that show a significant association with arthritis susceptibility and severity [ 3 - 6 ]. At least 52 QTLs have been identified in different rat models of arthritis, and these QTLs cover approximately 54% of the total rat genome [ 6 ].…”
Section: Genetic Linkage Studies For Adjuvant Arthritis-linked Quantimentioning
confidence: 99%
“…Studies in experimental models have identified many quantitative trait loci (QTLs) that show a significant association with arthritis susceptibility and severity [ 3 - 6 ]. At least 52 QTLs have been identified in different rat models of arthritis, and these QTLs cover approximately 54% of the total rat genome [ 6 ]. These QTLs are distributed among various chromosomes (including the X chromosome), except for chromosomes 11, 13 and 17, but at present there is no information about QTLs on the Y chromosome [ 6 ].…”
Section: Genetic Linkage Studies For Adjuvant Arthritis-linked Quantimentioning
confidence: 99%
“…Though the genes in Group A3 are associated with arthritis-QTL, the expression level in LEW and WKY rats are comparable. In regard to the genes under Group B1 and B2 (differentially expressed between LEW and WKY rats, but not associated with arthritis QTL), we suggest that this group of DEG should also be considered for further evaluation for its likely contribution to disease susceptibility in AIA (Brenner et al, 2006; Remmers et al, 1996; Xiong et al, 2008). …”
Section: Discussionmentioning
confidence: 94%
“…The procedures used were to that previous published [12]. Briefly, query terms were the combination of the name of the gene with any of these key words: arthritis, inflammation, anti-inflammatory, inflammatory mediator, inflammatory cytokine, autoimmune, immune, joint damage, T-cell, macrophage, neutrophil, angiogenesis, synovial, synovial hyperplasia, synovial fibroblast, lymphocytic infiltrate, and cartilage degradation.…”
Section: Methodsmentioning
confidence: 99%